Respuesta :
Answer:
It all relies on the operation being used and you have to work each problem step by step
Step-by-step explanation:
For example: Addition
What is +2+(-3)+(-3)?
So first thing to realise is that an addition sign + a negative sign - always equals to a negative sign. As shown here +(-3)=-3 because + and - when used together it always ends up being negative according to the rule. So the problem above works out to be +2+(-3)+(-3)=
+2-3-3
Work this step with this rule in Addition when adding or subtracting a positive and negative the resulting number always takes the sign of the bigger number .
So +2-3=-1 according to the rule .
When adding two negatives, add the numbers and place back the negative sign. So -3+(-1)=-4
So +2+(-3)+(-3)=-4
When Multiplying or dividing Positives + and negatives- the sign always results in a negative - But if you have two negatives - and -in multiplication and division the result is always a positive
Example
+2×-3=-6 and -2×-3=+6 Using the rule
So if you have
(1) -2×(+2)×(-2)
If you work this step by step
-2×(+2)=-4
thus (-4)×(-2)=+8 according to the rule
so the answer for number 1 is +8
And
-×+×+×-= positive
-2×(+2)×(+2)×(-2)=+16
However
-2×-2×-2×+2 cannot be positive 16 it must be negative 16 working it out step by step
-2×-2=+4×-2=-8×+2=-16
Same thing applies for division
In conclusion all you need to do is remember the rules and you will be fine.